5.24.9 Problems 801 to 900

Table 5.1031: Second or higher order ODE with non-constant coefficients

#

ODE

Mathematica

Maple

8842

\[ {}y^{\prime \prime }-x^{2} y-x^{4}+2 = 0 \]

8843

\[ {}y^{\prime \prime }-2 x^{2} y-x^{4}+1 = 0 \]

8844

\[ {}y^{\prime \prime }-x^{3} y-x^{3} = 0 \]

8845

\[ {}y^{\prime \prime }-x^{3} y-x^{4} = 0 \]

8846

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-x^{2} y-x^{2} = 0 \]

8847

\[ {}y^{\prime \prime }-x^{3} y^{\prime }-x^{3} y-x^{3} = 0 \]

8848

\[ {}y^{\prime \prime }-x y^{\prime }-x y-x = 0 \]

8849

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-x y-x^{2} = 0 \]

8850

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-x^{2} y-x^{3}-x^{2} = 0 \]

8851

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-x^{3} y-x^{4}-x^{2} = 0 \]

8852

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{x}-x y-x^{2}-\frac {1}{x} = 0 \]

8853

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{x}-x^{2} y-x^{3}-\frac {1}{x} = 0 \]

8854

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{x}-x^{3} y-x^{4}-\frac {1}{x} = 0 \]

8855

\[ {}y^{\prime \prime }-x^{3} y^{\prime }-x y-x^{3}-x^{2} = 0 \]

8856

\[ {}y^{\prime \prime }-x^{3} y^{\prime }-x^{2} y-x^{3} = 0 \]

8857

\[ {}y^{\prime \prime }-x^{3} y^{\prime }-x^{3} y-x^{4}-x^{3} = 0 \]

8858

\[ {}y^{\prime \prime \prime }-x^{3} y^{\prime }-x^{2} y-x^{3} = 0 \]

8873

\[ {}x^{4} y^{\prime \prime }+x^{3} y^{\prime }-4 x^{2} y = 1 \]

8874

\[ {}x^{4} y^{\prime \prime }+x^{3} y^{\prime }-4 x^{2} y = x \]

8875

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = x \]

8876

\[ {}x^{4} y^{\prime \prime \prime }+x^{3} y^{\prime \prime }+x^{2} y^{\prime }+x y = 0 \]

8877

\[ {}x^{4} y^{\prime \prime \prime }+x^{3} y^{\prime \prime }+x^{2} y^{\prime }+x y = x \]

8878

\[ {}5 x^{5} y^{\prime \prime \prime \prime }+4 x^{4} y^{\prime \prime \prime }+x^{2} y^{\prime }+x y = 0 \]

8879

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+1+{y^{\prime }}^{2} = 0 \]

8880

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+1+{y^{\prime }}^{2} = x \]

8881

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+1+x {y^{\prime }}^{2} = 1 \]

8882

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+y {y^{\prime }}^{2} = 0 \]

8883

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

8884

\[ {}y^{\prime \prime }+\sin \left (y\right ) {y^{\prime }}^{2} = 0 \]

8885

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+{y^{\prime }}^{3} = 0 \]

8888

\[ {}4 x^{2} y^{\prime \prime }+y = 8 \sqrt {x}\, \left (\ln \left (x \right )+1\right ) \]

8953

\[ {}\frac {x y^{\prime \prime }}{1-x}+y = \frac {1}{1-x} \]

8954

\[ {}\frac {x y^{\prime \prime }}{1-x}+x y = 0 \]

8955

\[ {}\frac {x y^{\prime \prime }}{1-x}+y = \cos \left (x \right ) \]

8956

\[ {}\frac {x y^{\prime \prime }}{-x^{2}+1}+y = 0 \]

8957

\[ {}y^{\prime \prime } = \left (x^{2}+3\right ) y \]

8961

\[ {}y^{\prime \prime } \sin \left (2 x \right )^{2}+y^{\prime } \sin \left (4 x \right )-4 y = 0 \]

8962

\[ {}y^{\prime \prime } = A y^{{2}/{3}} \]

8963

\[ {}y^{\prime \prime }+2 x y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

8964

\[ {}y^{\prime \prime }+2 \cot \left (x \right ) y^{\prime }-y = 0 \]

8965

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

8966

\[ {}4 x^{2} y^{\prime \prime }+\left (-8 x^{2}+4 x \right ) y^{\prime }+\left (4 x^{2}-4 x -1\right ) y = 4 \sqrt {x}\, {\mathrm e}^{x} \]

8967

\[ {}x y^{\prime \prime }-\left (2+2 x \right ) y^{\prime }+\left (x +2\right ) y = 6 \,{\mathrm e}^{x} x^{3} \]

8981

\[ {}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0 \]

8983

\[ {}y^{\prime \prime }+{\mathrm e}^{y} = 0 \]

9084

\[ {}{y^{\prime \prime }}^{2}+y^{\prime } = 0 \]

9085

\[ {}y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

9087

\[ {}{y^{\prime \prime }}^{2}+y^{\prime } = 1 \]

9088

\[ {}y^{\prime \prime }+{y^{\prime }}^{2} = 1 \]

9090

\[ {}{y^{\prime \prime }}^{2}+y^{\prime } = x \]

9091

\[ {}y^{\prime \prime }+{y^{\prime }}^{2} = x \]

9093

\[ {}{y^{\prime \prime }}^{2}+y^{\prime }+y = 0 \]

9094

\[ {}y^{\prime \prime }+{y^{\prime }}^{2}+y = 0 \]

9116

\[ {}y {y^{\prime \prime }}^{2}+y^{\prime } = 0 \]

9117

\[ {}y {y^{\prime \prime }}^{2}+{y^{\prime }}^{3} = 0 \]

9118

\[ {}y^{2} {y^{\prime \prime }}^{2}+y^{\prime } = 0 \]

9119

\[ {}y {y^{\prime \prime }}^{4}+{y^{\prime }}^{2} = 0 \]

9120

\[ {}y^{3} {y^{\prime \prime }}^{2}+y y^{\prime } = 0 \]

9121

\[ {}y y^{\prime \prime }+{y^{\prime }}^{3} = 0 \]

9122

\[ {}y {y^{\prime \prime }}^{3}+y^{3} y^{\prime } = 0 \]

9123

\[ {}y {y^{\prime \prime }}^{3}+y^{3} {y^{\prime }}^{5} = 0 \]

9124

\[ {}y^{\prime \prime }+x y^{\prime }+y {y^{\prime }}^{2} = 0 \]

9125

\[ {}y^{\prime \prime }+\sin \left (x \right ) y^{\prime }+y {y^{\prime }}^{2} = 0 \]

9126

\[ {}y^{\prime \prime }+\left (1-x \right ) y^{\prime }+y^{2} {y^{\prime }}^{2} = 0 \]

9127

\[ {}y^{\prime \prime }+\left (\sin \left (x \right )+2 x \right ) y^{\prime }+\cos \left (y\right ) y {y^{\prime }}^{2} = 0 \]

9128

\[ {}y^{\prime } y^{\prime \prime }+y^{2} = 0 \]

9129

\[ {}y^{\prime } y^{\prime \prime }+y^{n} = 0 \]

9131

\[ {}y^{\prime \prime }+\left (x +3\right ) y^{\prime }+\left (y^{2}+3\right ) {y^{\prime }}^{2} = 0 \]

9132

\[ {}y^{\prime \prime }+x y^{\prime }+y {y^{\prime }}^{2} = 0 \]

9133

\[ {}y^{\prime \prime }+\sin \left (x \right ) y^{\prime }+{y^{\prime }}^{2} = 0 \]

9134

\[ {}3 y^{\prime \prime }+\cos \left (x \right ) y^{\prime }+\sin \left (y\right ) {y^{\prime }}^{2} = 0 \]

9135

\[ {}10 y^{\prime \prime }+x^{2} y^{\prime }+\frac {3 {y^{\prime }}^{2}}{y} = 0 \]

9136

\[ {}10 y^{\prime \prime }+\left ({\mathrm e}^{x}+3 x \right ) y^{\prime }+\frac {3 \,{\mathrm e}^{y} {y^{\prime }}^{2}}{\sin \left (y\right )} = 0 \]

9137

\[ {}y^{\prime \prime }-\frac {2 y}{x^{2}} = x \,{\mathrm e}^{-\sqrt {x}} \]

9138

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{\sqrt {x}}+\frac {y \left (-8+\sqrt {x}+x \right )}{4 x^{2}} = x \]

9139

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x}+\frac {a^{2} y}{x^{4}} = 0 \]

9140

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }-c^{2} y = 0 \]

9141

\[ {}x^{6} y^{\prime \prime }+3 x^{5} y^{\prime }+a^{2} y = \frac {1}{x^{2}} \]

9142

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+3 y = 2 x^{3}-x^{2} \]

9143

\[ {}y^{\prime \prime }+\cot \left (x \right ) y^{\prime }+4 \csc \left (x \right )^{2} y = 0 \]

9144

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+\left (1+x \right ) y^{\prime }+y = 4 \cos \left (\ln \left (1+x \right )\right ) \]

9145

\[ {}y^{\prime \prime }+\tan \left (x \right ) y^{\prime }+\cos \left (x \right )^{2} y = 0 \]

9146

\[ {}x y^{\prime \prime }-y^{\prime }+4 x^{3} y = 8 x^{3} \sin \left (x \right )^{2} \]

9147

\[ {}x y^{\prime \prime }-y^{\prime }+4 x^{3} y = x^{5} \]

9148

\[ {}y^{\prime \prime } \cos \left (x \right )+\sin \left (x \right ) y^{\prime }-2 y \cos \left (x \right )^{3} = 2 \cos \left (x \right )^{5} \]

9149

\[ {}y^{\prime \prime }+\left (1-\frac {1}{x}\right ) y^{\prime }+4 x^{2} y \,{\mathrm e}^{-2 x} = 4 \left (x^{3}+x^{2}\right ) {\mathrm e}^{-3 x} \]

9150

\[ {}y^{\prime \prime }-x^{2} y^{\prime }+x y = x^{m +1} \]

9151

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{\sqrt {x}}+\frac {y \left (-8+\sqrt {x}+x \right )}{4 x^{2}} = 0 \]

9152

\[ {}\cos \left (x \right )^{2} y^{\prime \prime }-2 \cos \left (x \right ) \sin \left (x \right ) y^{\prime }+\cos \left (x \right )^{2} y = 0 \]

9153

\[ {}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-1\right ) y = -3 \,{\mathrm e}^{x^{2}} \sin \left (x \right ) \]

9154

\[ {}y^{\prime \prime }-2 b x y^{\prime }+b^{2} x^{2} y = x \]

9155

\[ {}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-3\right ) y = {\mathrm e}^{x^{2}} \]

9156

\[ {}y^{\prime \prime }-2 \tan \left (x \right ) y^{\prime }+5 y = {\mathrm e}^{x^{2}} \sec \left (x \right ) \]

9157

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 \left (x^{2}+1\right ) y = 0 \]

9158

\[ {}4 x^{2} y^{\prime \prime }+4 x^{5} y^{\prime }+\left (x^{8}+6 x^{4}+4\right ) y = 0 \]

9159

\[ {}x^{2} y^{\prime \prime }+\left (x y^{\prime }-y\right )^{2} = 0 \]

9160

\[ {}x y^{\prime \prime }+2 y^{\prime }-x y = 0 \]

9161

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

9168

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-5\right ) y = 0 \]

9169

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]